Overexpression of a Sucrose Synthase Gene Indirectly Improves Cotton Fiber Quality Through Sucrose Cleavage - Ahmed, Mukhtar; Iqbal, Adnan; Latif, Ayesha; Din, Salah ud; Sarwar, Muhammad Bilal; Wang, Xuede; Rao, Abdul Qayyum; Husnain, Tayyab; Ali Shahid, Ahmad (Frontiers in Plant Science, 2020)
The study aims to improve fiber traits of local cotton cultivar through genetic transformation of sucrose synthase (SuS) gene in cotton. Sucrose synthase (SuS) is an important factor that is involved in the conversion of sucrose to fructose and UDP-glucose, which are essential for the synthesis of cell wall cellulose. In current study, we expressed a synthetic SuS gene in cotton plants under the control of a CaMV35S promoter. Amplification of a 813 bp fragment using gene-specific primers confirmed the successful introduction of SuS gene into the genome of cotton variety CEMB-00. High SuS mRNA expression was observed in two transgenic cotton plants, MA0023 and MA0034, when compared to the expression in two other transgenic cotton plants, MA0035 and MA0038. Experiments showed that SuS mRNA expression was positively correlated with SuS activity at the vegetative (54%) and reproductive stages (40%). Furthermore, location of transgene was found to be at chromosome no 9 in the form of single insertion while no signal was evident in non-transgenic control cotton plant when evaluated through Fluorescent in Situ hybridization and karyotyping analysis. Fiber analyses of the transgenic cotton plants showed increases of 11.7% fiber length, 18.65% fiber strength, and up to 5% cellulose contents. An improvement in the micronaire value of 4.21 was also observed in the MA0038 transgenic cotton line. Scanning electron microscopy (SEM) revealed that the fibers of the SuS transgenic cotton plants were highly spiral with a greater number of twists per unit length than the fibers of the non-transgenic control plants. These results determined that SuS gene expression influenced cotton fiber structure and quality, suggesting that SuS gene has great potential for cotton fiber quality improvement.